Transgender Community and Its Slang Words - Siti Asiyah (Register Journal, 2014)
The purpose of this research is to describe slang words used in transgender community in Salatiga, the meaning, how to form and the functions. This is the descriptive qualitative method. The data are from natural communication taking among transgenders. The source of data is transgender community in the form of oral data. The results of the studyshows that transgender slang words is formed by borrowing syllables of Javanese and Indonesian language, adding with specific affixes, or changing into other common words. Transgender community inserts the slang words into Javanese language and use Javanese language structure to form their utterances. They use it as a secret code and also solidaritymarker inside the groups or between the group and other groups.Keywords: Slang words; Transgender community; Function of slang words